Digitalization of Financial Reports of Village-Owned Enterprises - Volta Diyanto; Putri Nabila Musfi (Indonesian Journal of Economics, Social, and Humanities, 2022)
This study aimed to describe to the optimization of the role of village-owned enterprises which will increase the village original income. Management of village potential becomes the basic needs of economic growth and equity. Therefore, it is necessary to maximize the role of village-owned enterprises to increase village original income. The research objectives are to design and create a web-based village-owned enterprises governance digitization system and to design and create a web-based village-owned enterprises financial reporting digitization system. The research population is the village-owned enterprises in Siberida District, Indragiri Hulu Regency. The research sample is Berkah Bersama village-owned enterprises. The data collection technique used primary data and secondary data, namely conducting interviews with the directors and employees of village-owned enterprises, as well as the public as users of information. While secondary data are in the form of Standard Operating Procedures (SOP), ministerial regulations, series 7 village fund guidebooks on village-owned enterprises. The conclusion of this study is the achievement of the result of web-based software application to design a financial management application through e-village budgeting that can help village-owned enterprises managers make transparent and accountable financial reporting.